Expressão gênica de proteínas associadas ao reparo de membrana e dinâmica do citoesqueleto de actina em mioblastos infectados pelo Trypanosoma cruzi - Tavares, Paula Cristina Brígido (2016)
Trypanosoma cruzi is the causative agent of Chagas disease, one of the most neglected tropical diseases. It is estimated that about 11 million people worldwide are infected with T. cruzi, about 6 million to 7 million people are estimated to be infected worldwide. During the molecules invasion process of the parasite and host interact allowing the signal transduction and modulation gene expression in response to invasion. The diversity of proteins and pathways triggered to repair wounded plasma membrane turned our attention to investigate the impact of T. cruzi infection in gene expression of Dysferlin, ASM, TFEB, Galectin 1 and 3, Annexin 1 and 2, by murine myoblasts. Thus we analyzed the expression of genes by quantifying the relative and parasitic load by real-time PCR. We conclude that our study found increased Dysferlin gene expression, ASM and TFEB during the invasion, kinetics for two hours by T. cruzi Y strain in myoblasts. Moreover treatment with Rapamycin inhibited mTOR signaling pathway, decreased cellular internalization and negatively regulating the expression of TFEB, ASM and Annexin A2 in myoblasts treated and infected as compared to myoblasts untreated with Rapamycin and infected. Our results show that during cell invasion by T. cruzi, host cell gene expression is modulated in response to the damage generated by the parasite.